Cerebrotendinous xanthomatosis-a case report with novel compound heterozygous mutation of CYP27A1 gene - Jeng Yuan; Pi-Shan Sung; Julia Yu-Yun Lee; Sheau-Chiou Chao (Wolters Kluwer Medknow Publications, 2018)
Cerebrotendinous xanthomatosis (CTX), a rare autosomal recessive lipid storage disorder which is caused by mutations in gene CYP27A1 leads to deficiency of enzyme sterol 27-hydroxylase. Clinically, CTX is characterized by tendon xanthomas, premature atherosclerosis, juvenile cataracts and progressive neurological deficits. In this study, we report one 34 year-old Taiwanese man who developed bilateral xanthomas on Achilles tendon and progressive neuropsychiatric disorder. DNA sequencing revealed novel compound heterozygous mutation of CYP27A1 gene, 1072C > T (Gln358X) in exon 6 and c.496-497, 503-514 deletion in exon 1. Early diagnosis of CTX is crucial because treatment with chenodeoxycholic acid in time may prevent or improve neurological dysfunction. Keywords: Cerebrotendinous xanthomatosis, Tendon xanthomas, CYP27A1